Effect of added carbon dioxide (CO2) conduction on root induction in cutting ball of Chiang-da shoots from tissue culture - Jantaramoon, Napawan; Chidburee, Piengpim; Chidburee, Aphichat (Health Science, Science and Technology Reviews, 2023)
The research aimed to study the effect of added carbon dioxide (CO2) conduction on root induction in cutting – ball of Chiang – da shoots from tissue culture. A completely randomized design (CRD) of five treatments with six replications was used in this experiment. Tr.1 ; Semi - medium bottle cap (control), Tr.2 ; cutting ball + standard lid, Tr.3 ; cutting ball + vented tissue culture cap, Tr.4 ; cutting ball + added CO2 + vented tissue culture cap and Tr.5 ; cutting ball + added CO2 + standard lid. The results showed that the shoot tip plants on Tr.2, Tr.3, Tr.4 and Tr.5 had the highest average survival percentage. The number of roots showed that cultured in control had the highest mean number of roots significantly different from other treatments. The percentage of a root, length of root, SPAD Unit, chlorophyll a, b and total were not significantly different from all treatments.